Representation of Nostalgic Memories for Home in African Diasporic Poetry: Critical Analysis of Selected Poems of Mahtem Shiferraw - Elias, Stanley (Universitas Sanata Dharma, 2018)
Nostalgia for home has been a common subject in African diasporic literature. In past four decades the African continent has witnessed an increase of movements of people leaving their home places to new places around the world. These movements whether voluntarily or forcibly have resulted to displaced communities in the world and diasporic community being one of those communities. This paper critically analyses the representation of nostalgic for home in selected poems in of Mahtem Shiferraw and how do such nostalgic memories contribute of in (re)defining the identity of the poet. Central to the analysis it can be argued that nostalgic memories are reflective and restorative of past experiences of home [land] crafted from diasporic sensibilities. As depicted in the selected poems, namely, â€œFuchsiaâ€, â€œSynesthesiaâ€ and â€œTalk about Raceâ€ the poet represents both the pleasant and unpleasant past life experiences she has gone through while in Africa and later in America. Also nostalgic memories re/defines the inseparable forged identity of the poet from reconstructed past as an African in America. However, according to the discussion, the traditional sense of nostalgia is challenged as the poet yearns for the significant moments of home [land] while remaining in the foreign land.Keywords: diasporic literature, home; nostalgic memoriesÂ